DOI: 10.17760/d20270105
|View full text |Cite
|
Sign up to set email alerts
|

From no to yes : the impact of an intervention on the persistence of algebraic misconceptions among secondary school algebra students

Abstract: Many students enter high school with persistent algebraic misconceptions that limit their success in mathematics and, by extension, limit potential educational attainment and future earnings.The purpose of this study was to assess the effectiveness of a warm conceptual change based intervention on remediating algebraic misconceptions held by students at a secondary school.The study used a quasi-experimental, pre-test post-test, control group design as well as student focus groups. In this eight-week classroom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…In addition, the non-refutation text condition had to contain the same general instructional information as the refutation text, meaning studies with no instructional materials (Heddy et al, 2017) or filler texts (Kendeou et al, 2014) as the non-refutation text conditions were excluded. Additional inclusion criteria were that the study had to quantitatively measure learning outcomes of factual information rather than beliefs or opinions; report enough data to accurately calculate an effect size; report the number of participants in the experimental and control groups, as this allowed for a meta-analysis examining clear, transparent data and the ability to report the refutation text and comparison group numbers for each comparison; use a research design with few or minimal confounding variables (e.g., Zielinski, 2017 was excluded as it seemed one could not plausibly conclude that the refutation text alone caused any difference that may have occurred); be published in English; and be publicly available.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…In addition, the non-refutation text condition had to contain the same general instructional information as the refutation text, meaning studies with no instructional materials (Heddy et al, 2017) or filler texts (Kendeou et al, 2014) as the non-refutation text conditions were excluded. Additional inclusion criteria were that the study had to quantitatively measure learning outcomes of factual information rather than beliefs or opinions; report enough data to accurately calculate an effect size; report the number of participants in the experimental and control groups, as this allowed for a meta-analysis examining clear, transparent data and the ability to report the refutation text and comparison group numbers for each comparison; use a research design with few or minimal confounding variables (e.g., Zielinski, 2017 was excluded as it seemed one could not plausibly conclude that the refutation text alone caused any difference that may have occurred); be published in English; and be publicly available.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Studies have revealed that students have difficulties in understanding the basic concepts of algebra and have misconceptions throughout their school life (Carraher, Schliemann, & Brizuela, 2005;Falkner, Levi & Carpenter, 1999, Stephens, 2008, and issues still apparent in the recent studies (Barbieri, Miller-Cotto & Booth, 2019;Mokh, 2019;Zielinski, 2017). According to Akkan, Baki & Çakıroğlu (2011), one of the main reasons for student difficulties is a cognitive gap possibly due to the rapid transition from the context of arithmetic to algebra.…”
Section: Introductionmentioning
confidence: 99%